The wyverns' treasure - LaFevers, R. L.; Murphy, Kelly, 1977- (Boston [Mass.] : Houghton Mifflin Books for Children, 2010)
When Nathaniel and Aunt Phil are summoned to the Welsh countryside to calm the giant dragons known as wyverns, they suspect the problem was caused by the same sinister man who has been trying to steal the Book of Beasts.
008-012.
Keywords: Adventure and adventurers -- Fiction; Aunts -- Fiction; Dragons -- Fiction; Animals, Mythical -- Fiction; Orphans -- Fiction; Wales -- Fiction; Dragons -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Orphans -- Juvenile fiction; Aunts -- Juvenile fiction; Wales -- Juvenile fiction